THE ROLE OF INNOVATIVE TECHNOLOGIES IN SOCIETY - qizi, Makhmatkulova Hikoyat Ghiyosiddin; qizi, Kholdarova Fotima Mahammadjon (PT ANTIS International Publisher, 2024)
This topic discusses the significance of innovative educational technologies in contemporary times. It provides information about the role of modern methods and technologies during the course of lessons.